R2D2: A scalable deep learning toolkit for medical imaging segmentation. (11th August 2020) - Guedria, Soulaimane; De Palma, Noël; Renard, Félix; Vuillerme, Nicolas
Summary: Deep learning has gained a significant popularity in recent years thanks to its tremendous success across a wide range of relevant fields of applications, including medical image analysis domain in particular. Although convolutional neural networks (CNNs) based medical applications have been providing powerful solutions and revolutionizing medicine, efficiently training of CNNs models is a tedious and challenging task. It is a computationally intensive process taking long time and rare system resources, which represents a significant hindrance to scientific research progress. In order to address this challenge, we propose in this article, R2D2, a scalable intuitive deep learning toolkit for medical imaging semantic segmentation. To the best of our knowledge, the present work is the first that aims to tackle this issue by offering a novel distributed versions of two well‐known and widely used CNN segmentation architectures [ie, fully convolutional network (FCN) and U‐Net]. We introduce the design and the core building blocks of R2D2. We further present and analyze its experimental evaluation results on two different concrete medical imaging segmentation use cases. R2D2 achieves up to 17.5× and 10.4× speedup than single‐node based training of U‐Net and FCN, respectively, with a negligible, though still unexpected segmentation accuracy loss. R2D2 offers not only an empirical evidence and investigates in‐depth the latest published works but also it facilitates and significantly reduces the effort required by researchers to quickly prototype and easily discover cutting‐edge CNN configurations and architectures.